Haemostatic chitosan coated gauze: in vitro interaction with human blood and in-vivo effectiveness. Issue 1 (December 2015) - Pogorielov, M.; Kalinkevich, O.; Deineka, V.; Garbuzova, V.; Solodovnik, A.; Kalinkevich, A.; Kalinichenko, T.; Gapchenko, A.; Sklyar, A.; Danilchenko, S.
Abstract Background Chitosan and its derivates are widely used for biomedical application due to antioxidative, anti-inflammatory, antimicrobial and tissue repair induced properties. Chitosan-based materials also used as a haemostatic agent but influence of different molecular weight and concentration of chitosan on biological response of blood cells is still not clear. The aim of this research was to evaluate interaction between human blood cells and various forms of chitosan-based materials with different molecular weight and chitosan concentration and prove their effectiveness on in-vivo model. Methods We used chitosan with molecular weight 200, 500 and 700 kDa and deacetylation rate 80-82 %. For chitosan impregnation of gauze chitosan solutions in 1 % acetic acid with different concentrations (1, 2, 3, 5 %) were used. We used scanning electron microscopy to obtain information about chitosan distribution on cotton surface; Erythrocyte agglutination test and Complete blood count test – for evaluation of interaction between blood cells and chitosan-based materials with different compound. In-vivo studies was performed in 20 Wistar rats to evaluate effectiveness of new dressing. Results Our data shown that chitosan can bind erythrocytes in concentration-depend manner that does not depend on its molecular weight. In addition, chitosan-based materials affect selectively human blood cells. Composition of chitosan with cotton materials does not change erythrocyte shape and does not cause agglutination. Conclusions Сotton-chitosan materials have higher adhesive properties to platelets that depend on molecular weight and concentration of chitosan. These materials also change platelets' shape that probable is one of the most important mechanisms of haemostatic effect. In-vivo studies have shown high effectiveness of 2 % 200 kDa chitosan for stop bleeding from arteries of large diameter.